Outcomes of patients enrolled in an antiretroviral adherence club with recent viral suppression after experiencing elevated viral loads - Joseph Sharp (Southern African Journal of HIV Medicine, 2019)
Background: Eligibility for differentiated antiretroviral therapy (ART) delivery models has to date been limited to low-risk stable patients.